Corporate cash holdings: causes and consequences - Amess, Kevin; Banerji, Sanjay; Lampousis, Athanasios (Elsevier, 2015)
The considerable growth in corporate cash holdings around the world has prompted scholarly interest. Consequently, there is now a large academic literature examining cash holdings and their impact on corporate outcomes and firm values. This article reviews and synthesizes the literature to offer insight into two primary motives to hold cash: precautionary and agency. We first present a stylized model that explores the trade-off in holding cash between these two motives and then examine empirical studies to determine how existing theories are supported by evidence using data from a variety of countries. In addition, we examine the effectiveness of a variety of corporate governance devices in curtailing cash holdings and also the extent to which these devices offer investors' confidence that cash will not be wasted. Finally, we discuss methodological and measurement issues associated with empirical cash holdings studies.